A quantitative description method for the mechanical behavior of soil-rock mixture as affected by water content - Du, Yuxiang; Fu, Xiaodong; Sheng, Qian; Zhang, Zhenping; Du, Wenjie; Ding, Haifeng; Liu, Tingting (Frontiers in Ecology and Evolution, 2023)
The mechanical properties of soil rock mixture (S-RM) are complex, especially the strength deterioration after encountering water, which readily leads to engineering instability. A series of large triaxial tests of S-RM with different water contents under various confining pressures were performed, the mechanical properties of S-RM were explored from a macroscopic perspective. The constitutive model of S-RM – an extended Duncan-Chang (DC) model considering water content – was developed. The results show that: (a) the stress-strain curves of S-RM are strain hardening type, the peak strength decreases non-linearly with the increase of water content, the higher the water content of sample, the more significant the bulging phenomenon and the more numerous and extensive the surface cracks; (b) the cohesion c and internal friction angle φ of S-RM both decrease approximately linearly with the increase of water content, and the secant modulus decreases significantly with the increase of water content, the reason of which can be attributed to the porosity and compression characteristics of S-RM; (c) the extended DC model can be used to describe the mechanical behavior of S-RM affected by water under triaxial test conditions. The material constant K, failure ratio Rf, c, and φ are all related to water content ω, while material constant n is independent, only ω, n, maximum principal stress σ1, and minimum principal stress σ3 are needed to determine the tangent modulus of the DC model of S-RM. The results can provide an experimental basis and mechanical understanding applicable to engineering practice in an S-RM formation.